Cannabis roots: Pharmacological and toxicological studies in mice. (10th May 2021) - Lima, Kátia Simoni Bezerra; Silva, Maria Eduarda Gomes da Cruz; Araújo, Tarcísio Cícero de Lima; Silva, Clodoaldo Plácido da Fonseca; Santos, Balbino Lino; Ribeiro, Luciano Augusto de Araújo; Menezes, Pedro Modesto Nascimento; Silva, Mariana Gama; Lavor, Érica Martins; Silva, Fabrício Souza; Nunes, Xirley Pereira; Rolim, Larissa Araújo
Abstract: Ethnopharmacological relevance: There are many studies and therapeutic properties attributed to the flowers and leaves of the Cannabis species, but even with few pharmacological studies, Cannabis sativa L. (Cannabaceae) roots presents several therapeutic indications in folk medicine. Aim of the study: This study aimed to evaluate the anti-inflammatory and spasmolytic effects as well as the toxicological profile of the aqueous extract of Cannabis sativa roots (CsAqEx) in mice. Materials and methods: We assessed the anti-inflammatory effect with carrageenan-induced leukocyte migration assay, and carrageenan and histamine-induced paw edema methods; The spasmolytic effect was assessed through in vitro assays with isolated mice trachea. To assess motor coordination and mobility, mice went through the rotarod and open field tests, respectively. For the single-dose toxicity study, we administered CsAqEx at the dose of 1000 mg/kg by gavage. In a repeated dose toxicity study, animals received CsAqEx at doses of 25 mg or 100 mg/kg for 28 days. Results: The CsAqEx inhibited the migration of leukocytes at the doses of 25, 50, and 100 mg/kg. The CsAqEx showed anti-inflammatory activity after the intraplantar injection of carrageenan, presenting a reduction in edema formation at all tested doses (12.5, 25, 50 and 100 mg/kg). The dose of 12.5 mg/kg of CsAqEx prevented edema formation after intraplantar injection of histamine. In an organ bath, 729 μg/mL of CsAqEx did not promote spasmolytic effect on isolated mice tracheal rings contracted by carbachol (CCh) or potassium chloride (KCl). We did not observe clinical signs of toxicity in the animals after acute treatment with CsAqEx, which suggested that the median lethal dose (LD50 ) is greater than 1000 mg/kg. Repeated dose exposure to the CsAqEx did not produce significant changes in hematological, biochemical, or organ histology parameters. Conclusions: The results suggest that the anti-inflammatory effect of CsAqEx is related to the reduction of vascular extravasation and migration of inflammatory cells, without effects on the central nervous system. Moreover, there was no spasmolytic effect on airway smooth muscle and no toxicity was observed on mice. Graphical abstract: Image 1 Highlights: Cannabissativine is the main component of aqueous extract of Cannabis sativa roots (CsAqEx). The CsAqEx roots present anti-inflammatory activity in mice models of inflammation. However, it showed no spasmolytic effect on mice isolated trachea. The CsAqEx did not change motor coordination and locomotor activity in mice. The CsAqEx did not present toxic effects.